INQUIRY LEARNING AND COLLABORATIVE LEARNING STRATEGIES IN TEACHING WRITING WITHIN A GAME-BASED LEARNING FRAMEWORK - Roki Ranjani Sanjadireja, - (2019)
The implementation of video games in education has increased in the last decades. It is imperative to cope with the changes to develop technological pedagogy using video games in the classroom. Regardless the extensive research on using game in the writing classroom, which strategy the teachers used in the classroom remains unknown. This study aims to measure the implementation of game in the classroom with two different strategies: inquiry and collaborative strategies. The design of the study is a mixed method explanatory design with 37 students purposively selected at the higher education level. The samples are divided into three groups: the GBL with inquiry strategies, GBL with collaborative strategies, and control group without GBL. Both experiment groups experienced 'Transformational Play' framework. To compare the means between groups, the statistical analysis used is ANOVA and post hoc analysis. The post hoc result revealed that the mean score of GBL with inquiry strategies was significantly higher compared to the control group, however, GBL with collaborative strategies is not significantly different compared to the control group, and GBL with collaborative strategies is not significantly different compared to GBL with inquiry strategies. The observation reveals that the collaborative group needs more preparation for learning and specific strategy for collaborative-competitive environment. Although the collaborative group is not significantly different compared to the control group, the students' learning experience was positive according to Flow Condition Questionnaire and the structured interview. The students felt that learning with GBL was challenging, fun, serious, and easy to follow.